Development of Rules Concerning Indonesian Marriage Agreements - Widanarti, Herni; Benuf, Kornelius (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This study aims to examine the legal consequences caused by the marriage bond between a man and a woman, namely for the sake of law there is a mixture of assets between the two. This mixing of treasures led to the emergence of common property. However, there are exceptions to this mixture of assets, namely assets obtained before marriage, assets obtained based on gifts and assets obtained based on inheritance. So even though the mixing of assets occurs by law, it does not mean that this situation cannot be avoided. The existence of a marriage agreement that explicitly separates the assets of husband and wife in marriage. By entering into a Marriage Agreement, the two prospective husband and wife are entitled to prepare some deviations from the laws and regulations regarding the association of assets, as long as the agreement does not violate good morals or general rules and as long as all provisions are respected. This article will analyze and discuss the development of regulations regarding Marriage Agreements in Indonesia.